Angiographic Restenosis in Coronary Bifurcations Treatment with Regular Drug Eluting Stents and Dedicated Bifurcation Drug-Eluting BiOSS Stents: Analysis Based on Randomized POLBOS I and POLBOS II Studies - Robert J. Gil; Jacek Bil; Adam Kern; Luis A. Iñigo-Garcia; Radoslaw Formuszewicz; Slawomir Dobrzycki; Dobrin Vassilev; Roxana Mehran (Cardiovascular Therapeutics)
Aim. The marked variation in bifurcation anatomy has brought about an ongoing search for stents specifically constructed for coronary bifurcations. This study aimed to analyze the angiographic restenosis prevalence and patterns and predictors of different patterns in dedicated bifurcation BiOSS® vs. current generation drug-eluting stents implanted in coronary bifurcation lesions based on data from two clinical trials POLBOS I and II. Methods. Dedicated bifurcation BiOSS® stents were compared with drug-eluting stents (DES) in patients with stable coronary artery disease (CAD) or nonST elevation acute coronary syndrome (NSTE-ACS) (POLBOS I: paclitaxel eluting BiOSS® Expert vs. DES; POLBOS II: sirolimus eluting BiOSS® LIM vs. DES). Provisional T-stenting was the default treatment. Morphological pattern of in-stent restenosis according to the modified Mehran classification adopted for bifurcation lesions was assessed with bifurcation dedicated quantitative coronary angiographic software (CAAS 5.11, Pie Medical Imaging BV, the Netherlands). Results. In total, 445 patients (222 patients in BiOSS group and 223 patients in DES group) were included into the analysis. In BiOSS group 24 cases of angiographic restenosis (10.8%) were recorded, and in DES group—17 cases (7.6%) at 12 months follow-up (angiographic control rate at follow-up—90.3%). In the BiOSS group most frequent medina classification in restenotic cases was 0.0.1 (25%), whereas in DES—0.0.1 and 0.1.1 (23.5% each). In multivariate regression analysis proximal optimization technique was associated with the lowest chance for restenosis (OR 0.15, 95% CI 0.06–0.33), whereas diabetes on insulin was associated with the highest risk of restenosis (OR 4.21, 95% CI 1.48–11.44). Conclusions. The angiographic restenosis pattern and rate was similar between BiOSS stents and DES in coronary bifurcation lesions.